2017
DOI: 10.1186/s13287-017-0721-0
|View full text |Cite
|
Sign up to set email alerts
|

Paracrine effects of human amniotic epithelial cells protect against chemotherapy-induced ovarian damage

Abstract: BackgroundHuman amniotic epithelial cells (hAECs) are attractive candidates for regenerative medical therapy, with the potential to replace deficient cells and improve functional recovery after injury. Previous studies have demonstrated that transplantation of hAECs effectively alleviate chemotherapy-induced ovarian damage via inhibiting granulose cells apoptosis in animal models of premature ovarian failure/insufficiency (POF/POI). However, the underlying molecular mechanism accounting for hAECs-mediated ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 39 publications
7
64
0
3
Order By: Relevance
“…8 ). These current findings are consistent with the results of a previous study showing that mesenchymal stem cells recover the ovarian function of POI by regulating the SMAD pathway [ 25 ]. Several lines of evidence support this result and indicate that SMAD knockdown induced follicle loss by increasing the expression levels of apoptosis genes (Fas, FasL, caspase-3, and caspase-8) [ 19 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…8 ). These current findings are consistent with the results of a previous study showing that mesenchymal stem cells recover the ovarian function of POI by regulating the SMAD pathway [ 25 ]. Several lines of evidence support this result and indicate that SMAD knockdown induced follicle loss by increasing the expression levels of apoptosis genes (Fas, FasL, caspase-3, and caspase-8) [ 19 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…12,31 Many studies have shown that the activation of the CB2 receptor causes immunomodulatory eff ects. 24,32 As in previous studies with paracrine, 33 it was observed that the cytokine levels produced by ovarian damage were reduced by the activation of the CB2 receptor agonist. Recent studies with the activation of the CB2 receptor agonist on some diseases such as asthma, colitis, rheumatoid arthritis, rat paw infl ammation, and infl ammatory bowel disease show that it inhibits proinfl ammatory cytokine production, such as TNF-α and IL-1β, and protects it from ovarian injuries.…”
Section: Discussionsupporting
confidence: 53%
“…Another recent study used an alternative stem cell source: endometrial mesenchymal stem cells (MSCs) injected into mice with chemo-induced POI resulted in higher circulating levels of anti-Mullerian hormone (AMH, a known marker of ovarian reserve), greater number of developing follicles, and higher ovulation and live birth rates 46 . Furthermore, the therapeutic benefit of stem cells from other tissues, including adipose, umbilical cord blood, and amniotic epithelial cells, has been explored [47][48][49][50] . Recent research has begun to explore how stem cells specifically affect the ovarian microenvironment and restore ovarian function through the use of exosomes derived from stem cells in chemotherapy-induced POI models 51,52 .…”
Section: Foxl2mentioning
confidence: 99%